Let
be vectors pointing the vertices K, L, M, and N, respectively.
The side KL is parallel to and has the same length as the vector
![\vec L - \vec K = (2\,\vec\imath + 3\,\vec\jmath + 3\,\vec k) - (2\,\vec\imath+2\,\vec\jmath+\vec k) = \vec\jmath + 2\,\vec k](https://img.qammunity.org/2023/formulas/mathematics/high-school/xeq3vwjk1dde2xtl4lz2n8e9vej9u41uws.png)
Similarly, the side KN is parallel and as long as
![\vec N - \vec K = (6\,\vec\imath+8\,\vec\jmath+\vec k) - (2\,\vec\imath+2\,\vec\jmath+\vec k) = 4\,\vec\imath+6\,\vec\jmath](https://img.qammunity.org/2023/formulas/mathematics/high-school/a4pvav9xhthbz0qrallp707n3sap1q73x2.png)
These vectors have magnitudes
![\|\vec L - \vec K\| = √(0^2 + 1^2 + 2^2) = \sqrt5](https://img.qammunity.org/2023/formulas/mathematics/high-school/fdr71ipmq9y6642i5f7jkr23otwy3x23jb.png)
![\|\vec N - \vec K\| = √(4^2 + 6^2 + 0^2) = 2√(13)](https://img.qammunity.org/2023/formulas/mathematics/high-school/q49tqkk52h7bn7q8nq00ysjl7hjli72zhw.png)
and their dot product is
![(\vec L - \vec K) \cdot (\vec N - \vec K) = 0\cdot4 + 1\cdot6+1\cdot0 = 6](https://img.qammunity.org/2023/formulas/mathematics/high-school/xoavrahjem2qe875qob3ex7h0qwadygfgu.png)
The parallelogram spanned by the vectors
and
has area equal to the magnitude of their cross product, for which we have the identity
![\bigg\|(\vec L - \vec K) * (\vec N - \vec K)\bigg\| = \|\vec L - \vec K\| \|\vec N - \vec K\| \sin(\theta) \\\\ \implies \text{area} = 2√(65) \, \sin(\theta)](https://img.qammunity.org/2023/formulas/mathematics/high-school/4skygkywwez4xjbqn48b22blmxng7q7ne4.png)
where
is the angle between the sides KL and KN.
From the dot product identity, we have
![(\vec L - \vec K) \cdot (\vec N - \vec K) = \|\vec L - \vec K\| \|\vec N - \vec K\| \cos(\theta) \\\\ \implies 6 = 2√(65) \cos(\theta)](https://img.qammunity.org/2023/formulas/mathematics/high-school/jgf189niyx1yt6cs9yzk6z4e13e29kjfi1.png)
Then
![\cos(\theta) = \frac3{√(65)} \implies \sin(\theta) = √(1-\cos^2(\theta)) = 2\sqrt{(14)/(65)} \\\\ \implies \text{area} = 2√(65) \cdot 2\sqrt{(14)/(65)} = \boxed{4√(14)}](https://img.qammunity.org/2023/formulas/mathematics/high-school/q6te3l47sc6017x2lzcdp2dm2rz97r0xhy.png)